Legal Awareness Among Small and Medium-Sized Food Business Owners Producing Melinjo Crackers Regarding the Possession of a Busines Identification Number (NIB) in Blitar Regency - Hana Safitri; Eny Sulistyowati (Universitas Negeri Surabaya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to national economic development, particularly in strengthening the real sector and creating employment opportunities. Each year, the number of MSMEs continues to increase, including those in the food sector, which is rapidly growing across various regions. However, this growth is not accompanied by adequate legal awareness, as evidenced by the fact that many MSME actors in Blitar Regency still do not possess a Business Identification Number (NIB). In fact, ownership of an NIB is a legal obligation for MSMEs in accordance with Government Regulation No. 7 of 2021 concerning the Facilitation, Protection, and Empowerment of Cooperatives and Micro, Small, and Medium Enterprises. This study aims to analyze the legal awareness of MSME actors engaged in melinjo chip snack food processing regarding NIB ownership in Blitar Regency. The research employed an empirical juridical method. Data were collected through interviews, observations, and documentation, and were analyzed using a qualitative approach. The findings indicate that the legal awareness of these MSME actors is influenced by age, educational background, and social environment.